Comprehensive treatment of the macular edema in patients with retinal vein occlusion and hemostasis system disturbances - T.V. Shelkovnikova; Kh.P. Takhchidi; G.V. Vavin; N.Yu. Barkova; N.Yu. Shishlyannikova (РМЖ "Клиническая офтальмология")
T.V. Shelkovnikova1, Kh.P. Takhchidi2, G.V. Vavin3, N.Yu. Barkova1, N.Yu. Shishlyannikova3 1 Kemerovo Regional Clinical Ophthalmological Hospital, Kemerovo, Russian Federation 2 Pirogov Russian National Research University, Moscow, Russian Federation 3 Kemerovo State Medical University, Kemerovo, Russian Federation Aim: to study clinical and laboratory disturbances in the hemostasis system, the level of vascular endothelial growth factor (VEGF) and the clinical and morphometric parameters of macular edema (ME) in patients with retinal vein occlusion (RVO) and the level of lupus anticoagulant (LA) before and after comprehensive treatment. Patients and Methods: 135 patients (140 eyes) with occlusion of retinal veins (RVO) underwent an ophthalmologic examination and a study of some parameters of the hemostatic system. Detection of LA was performed using toxic tests, as well as confirmatory tests with donor plasma and corrective phospholipids. The study of the blood serum of patients on VEGF was carried out by enzyme immunoassay (ELISA). The comprehensive treatment of ME in accordance with patent RU No. 2614105-C1-2015 and discrete plasmapheresis was carried out. Results: in all patients with RVO and ME before and after comprehensive treatment, deviations from the normal hemostasis parameters and endothelial dysfunction of von Willebrand factor, activated protein C, VIII factor, VEGF were detected. LA was found in 23.6% of cases in patients with RVO. LA significantly reduces the thromboresistance of the endothelium of the retinal microvasculature and enhances hypercoagulation, breaks the natural regulation of the hemostasis system and aggravates retinal ischemia. LA exacerbates endothelial dysfunction in the microvasculature, supports autoimmune inflammation and is involved in the pathogenesis of ME, epiretinal membrane in patients with RVO. The proposed comprehensive treatment of LA reduces the thrombogenic activity in the retinal microvasculature, the capillary permeability of the retina, helps to improve lymphatic efflux, which leads either to the resolution of the ME or to a decrease in the retinal thickness of the macula. Conclusion: patients with ME need to undergo not only an ophthalmologic monitoring, but also the studies of procoagulants and anticoagulants of the hemostasis system, and the presence of LA and VEGF in the patient’s blood. This will allow prescribing timely adequate anticoagulant, antiplatelet, antioxidant therapy and discrete plasmapheresis. Key words: retinal vein occlusion, macular edema, hemostasis, vascular endothelial growth factor, VEGF, lupus anticoagulant. For citation: Shelkovnikova T.V., Takhchidi Kh.P., Vavin G.V. et al. Comprehensive treatment of the macular edema in patients with retinal vein occlusion and hemostasis system disturbances. RMJ “Clinical ophthalmology”. 2018;4:203–208.